Genome-Wide Characterization of Salt-Responsive miRNAs, circRNAs and Associated ceRNA Networks in Tomatoes - Zhongyu Wang (MDPI AG, 2021)
Soil salinization is a major environmental stress that causes crop yield reductions worldwide. Therefore, the cultivation of salt-tolerant crops is an effective way to sustain crop yield. Tomatoes are one of the vegetable crops that are moderately sensitive to salt stress. Global market demand for tomatoes is huge and growing. In recent years, the mechanisms of salt tolerance in tomatoes have been extensively investigated; however, the molecular mechanism through which non-coding RNAs (ncRNAs) respond to salt stress is not well understood. In this study, we utilized small RNA sequencing and whole transcriptome sequencing technology to identify salt-responsive microRNAs (miRNAs), messenger RNAs (mRNAs), and circular RNAs (circRNAs) in roots of M82 cultivated tomato and Solanum pennellii (S. pennellii) wild tomato under salt stress. Based on the theory of competitive endogenous RNA (ceRNA), we also established several salt-responsive ceRNA networks. The results showed that circRNAs could act as miRNA sponges in the regulation of target mRNAs of miRNAs, thus participating in the response to salt stress. This study provides insights into the mechanisms of salt tolerance in tomatoes and serves as an effective reference for improving the salt tolerance of salt-sensitive cultivars.